A wideband compact horizontally polarized omnidirectional antenna for 2G/3G/LTE. Issue 5 (1st February 2018) - Cai, Yuan‐Ming; Li, Wenting; Hu, Wei; Yin, Yingzeng
Abstract: A compact horizontally polarized omnidirectional slot antenna with a wide working band is presented in this article. The proposed antenna consists of 4 shorter driven cross‐shaped slots, 4 longer parasitic cross‐shaped slots, and a feeding network. Four shorter slots, placed on the same side of a circular substrate, are fed by a feeding network printed on the other side with uniform phase and magnitude. To enhance the bandwidth of the antenna, 4 longer cross‐shaped slots are inserted between adjacent longer slots to produce an additional resonant frequency. All 8 slot radiators placed symmetrically along the circumference results in an omnidirectional horizontal polarized radiation pattern. By utilizing cross‐shaped slots, a compact size of 0.53λL × 0.53λL × 0.005λL (λL is the free space wavelength at the lowest operational frequency) is achieved. The prototype of the proposed antenna is fabricated and measured. The measured results reasonably agree with the simulated results. The measured working band for |S11 |<–10dB is from 1.62 to 2.81 GHz which successfully covers the 1.7 to 2.7 GHz 2G/3G/LTE bands. The measured gain variation in azimuthal angle is <1.7 dB within 1.7 to 2.7 GHz, and the cross polarization level is <–27 dB in the horizontal plane.